HUBUNGAN EFEKTIVITAS PROGRAM RUSUNAWA TERHADAP KELAYAKAN RUMAH BAGI MASYARAKAT BERPENGHASILAN RENDAH (MBR) JAKARTA TIMUR - Hilmy Yahya; Eka Yulyana; Kariena Febriantin (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
This study aims to determine the relationship between the effectiveness of the simple rental apartment (Rusunawa) development program and the suitability of housing for low-income communities (MBR) in East Jakarta. The method used in this study is quantitative with an explanatory approach, as there are two variables used, namely independent and dependent variables. This is seen through the independent variable indicators (program effectiveness), namely program understanding, targeting, timeliness, achievement of objectives, and tangible changes. In addition, it is also seen through dependent variable indicators (housing affordability), namely building durability, living space, and access to clean water and sanitation. The results of the study, based on questionnaires filled out by respondents who are residents of the Rawabebek Rusunawa in East Jakarta, show that the Rusunawa development program has been implemented quite well and has met the expectations of the beneficiary community. Respondents also felt that the Rusunawa development program has not only succeeded in providing affordable housing, but also pays attention to the physical quality and comfort of housing for low-income communities. These findings provide an overview of the strategic policy implications for local governments to adopt the Sustainable Development Goals (SDGs) eligibility standards as the main parameters in evaluating vertical housing programs.